Synthesis, structure, and photophysics of copper(i) triphenylphosphine complexes with functionalized 3-(2′-pyrimidinyl)-1, 2, 4-triazole ligands. Issue 38 (25th September 2017) - Chen, Jing-Lin; Zeng, Xue-Hua; Luo, Yan-Sheng; Wang, Wan-Man; He, Li-Hua; Liu, Sui-Jun; Wen, He-Rui; Huang, Shuping; Liu, Li; Wong, Wai-Yeung
Abstract : The use of CF3 group can enhance the solid-state luminescence of 1, 2, 4-triazole-based Cu(i ) complexes but the use of Bu t and pyrimidinyl groups and the 1, 2, 4-triazolyl-NH deprotonation do not favor this. Abstract : A series of new mononuclear and dinuclear copper(i ) triphenylphosphine complexes with functionalized 3-(2′-pyrimidinyl)-1, 2, 4-triazole ligands have been synthesized and characterized, in which functionalized 3-(2′-pyrimidinyl)-1, 2, 4-triazole adopts neutral mono- and bis-chelating coordination modes and a mono-anionic bis-chelating binding manner due to the 1, 2, 4-triazolyl-NH deprotonation. All these Cu(i ) complexes display a relatively weak low-energy absorption in a CH2 Cl2 solution, ascribed to the charge-transfer transitions with appreciable MLCT character, as suggested by TD-DFT analyses. These Cu(i ) complexes are all emissive in solution and in the solid state at ambient temperature, and their luminescence properties can be well modulated via the addition of the second Cu(PPh3 )2 unit and modification of 3-(2′-pyrimidinyl)-1, 2, 4-triazole involving the N–H deprotonation and the substituent variation of the 1, 2, 4-triazolyl ring. It is also demonstrated that introducing the trifluoromethyl group into the 1, 2, 4-triazolyl ring is helpful for enhancing the solid-state luminescence properties of the 1, 2, 4-triazole-based Cu(i ) complexes, whereas the introduction of the tert -butyl group into the 1, 2, 4-triazolyl ring, the 1, 2, 4-triazolyl-NH deprotonation, and the use of the pyrimidinyl ring instead of the pyridyl ring are all unfavorable.